Physical - chemist analysis and influence of dissolved minerals on the tap water taste from Quito´s principals treatment plants - Torres-Silva, Stephanie; Tapia-Calvopiña, Ivan; Goetschel, Maria Lorena; Pazmiño-Salazar, Edgar (Enfoque UTE, 2020)
Drinking water flavor is influenced by some dissolved substances like Na+, K+, Fe3+, Cu2+, Ca2+, Mg2+, HCO3-, NO3-, Cl-, SO42- and CaCO3. This research was conducted in the Public Metropolitan Water and Sanitation Company or EPMAPS (for its acronym in Spanish) which is in charge of water purification and distribution in Quito. It was taken samples from six different treatment plants during five weeks and the following analysis were made: Sensory analysis executed by a panel of trained judges, who evaluated the acceptance ratio (FRA Test (Flavor Rating Assessment)) and the satisfaction ratio (Hedonic Test), physiochemical parameters determination and dissolved minerals concentration. Later the minerals concentration was correlated with the water’s flavor through a multiple factor analysis with main components analysis. As a result of this correlation, it was evidenced that the dissolved mineral concentration directly influences on the tap water flavor and determined statistically that the best sensory analysis is the Hedonic Test. Only the water from the treatment plant number 2 (PT2) obtained a lower sensorial valuation, whose flavor was described as lightly salted, which is related to its concentration of Ca2+, Mg2+, Na+, K+, HCO3-, CaCO3 y Cl-.